A DISCOURSE ANALYSIS OF INVITATION LETTERS IN ENGLISH AND VIETNAMESE - Ph.D. Trần Quang Hải (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Using a corpus of 500 invitation letters (ILs) in both languages – English and Vietnamese, with the light of discourse analysis, the study aims at investigating into ILs in English and Vietnamese in terms of layouts, lexical features, syntactic features and pragmatic features. The study also aims to explore the main similarities and differences between English invitation letters (EILs) and Vietnamese invitation letters (VILs) in the above terms. With regard to layout, the study goes deeply into the five parts forming an invitation letter (IL): heading, greeting, body, closing and signature. In terms of linguistic features, the thesis pays attention to three aspects: semantics, syntax and pragmatics. Semantically, the study finds out the use of personal pronoun, modal adverbs and transitions, then explores the role of these types of words in EILs and VILs. Syntactically, the study analyses the structures of invitations, the use of imperative mood, and the passive voice in ILs in the both languages. Pragmatically, politeness strategy is expected to be an important factor in writing ILs. Based on the Brown & Levinson (1987)’s theory of politeness, the study lays great emphasis on how positive and negative politeness strategies are used in ILs. After describing, classifying then analyzing the layout, lexical, syntactic, and pragmatic features of ILs in English and Vietnamese, we compare and contrast the above linguistic aspects to find out the similarities and differences between the two languages. On the basis of the findings, the thesis sets out some implications and suggestions for teaching and learning English as a foreign language in Vietnam. The research result can be helpful for teachers, learners of English as well as those who are interested in letter writing, especially invitation letter writing.